Representation of Female Leadership in the Film Hati Suhita: A Study of the Character of Alina in an Islamic Boarding School - Shofiatun Nafiah; Syairil Fadli; Nurliana (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Women's leadership in Islamic boarding schools continues to face challenges due to a patriarchal culture that positions men as central figures. This research aimed to analyze the representation of women's leadership through the character of Alina Suhita in the film Hati Suhita (2023). The research employed a descriptive qualitative approach using John Fiske's semiotic analysis, which covered the levels of reality, representation, and ideology. The analysis was strengthened by Stuart Hall's representation theory and Alice Eagly's Role Congruity Theory to understand how women are constructed as leaders in religious spaces. The findings revealed that Alina's leadership was represented in three dimensions: intellectual, emotional, and social. Intellectual leadership was seen when Alina provided historical knowledge to the students, affirming women's intellectual capacity in education. Emotional leadership was reflected in her ability to build interpersonal relationships and gain legitimacy through the support of family and Islamic boarding schools. Social leadership was demonstrated by the collective recognition of her authority by teachers and students. This research highlighted that the film Hati Suhita offered resistance to the patriarchal structure of Islamic boarding schools and opened discussions on the legitimacy of women's leadership.